Nurses' Knowledge and Practicing Level of Cognitive Behavioral Pain Relief Methods in Public Hospitals of Eastern Ethiopia. (November 2022) - Kibret, Haregeweyn; Assefa, Nega; Eyeberu, Addis; Debella, Adera; Getachew, Tamirat; Deressa, Alemayehu; Tamiru, Dawit; Bekele, Habtamu; Habte, Sisay; Teji, Kedir
Introduction: Despite the fact that cognitive behavioral therapy is regarded as a superior pain relief method and an alternative to drug therapy, little is known about its scope of application and determinant factors. As a result, the study sought to assess nurses' knowledge and practicing level of cognitive behavioral pain relief methods in public hospitals in eastern Ethiopia. Objective: To assess the knowledge and practicing level of cognitive behavioral pain relief among nurses working in public hospitals of eastern Ethiopia. Methods: A cross-sectional study was conducted among randomly selected 390 nurses. The data were collected using a self-administered questionnaire. The data were entered into Epi-data 3.1 and exported to SPSS 22 for analysis. Bivariate and multivariate logistic regression models were used to identify factors associated with cognitive behavioral therapy. Result: In this study, more than half (54.1%) of the respondents had good cognitive behavioral methods practicing levels. Nearly two-thirds (58.8%) of the participants had adequate knowledge about pain relief methods. Having adequate knowledge (adjusted odds ratio [AOR] 2.664; 95% confidence interval [CI]: 1.75, 4.7), having training (AOR 1.7; 95% CI: 1.03, 3.01), and positive attitude (AOR 4.02; 95% CI: 4.5, 12.4) were significantly associated with cognitive behavioral therapy. Conclusion: In this study, more than half of nurses had good cognitive behavioral methods practicing levels. Having a positive attitude, being knowledgeable, and having training were determinant factors in the practice of cognitive behavioral therapy. Continuing education and training should be considered for nurses to enhance their cognitive behavioral therapy practice.